ANALISIS PENGARUH QUICK RATIO TERHADAP RETURN ON EQUITY PADA CV. GRAHA MINERAL SIBOLGA - Gultom, Yusril Amin; Pohan, Safriadi; Panggabean, Yusi Tri Utari (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This study aims to examine the effect of the quick ratio on the return on equity (ROE) at CV. Graha Mineral Sibolga. The author uses research methods in quantitative descriptive to discuss the problems faced by corporate finance. Data analysis described the use of the results of several linear sub-data analyzes regarding the quick ratio (current ratio) to return on equity (ROE) (Y). The results showed that there was a positive relationship between the quick ratio and return on equity on CV. Graha Mineral Sibolga is 0.206, so when interpreted on a value scale it can be categorized as low. The regression equation obtained Y = 1.329 + 0.319X which shows the effect of the quick ratio on return on equity at CV. Graha Mineral Sibolga. The t test shows that the hypothesis proposed is rejected (not significant), where t count is 0.365 > 2.07387, which means that the return on equity does not necessarily increase as much as the regression coefficient/slop (0.319) if the quick ratio variable is added by one unit. While the coefficient of determination is known that the quick ratio only contributes 4.2% to the return on equity at CV. Graha Mineral Sibolga and the remaining 95.8% is influenced by other factors not included in the model.